Efficacy and safety evaluation of first-line systemic treatments for unresectable esophageal squamous cell carcinoma: a network meta-analysis - Shi, Huiling; Tan, Yong; Ma, Chao; Wei, Yushan; Shi, Fengling; Wang, Juan; Xu, Caihua; Liang, Rongrui (Frontiers in Oncology, 2024)
ObjectiveTo evaluate the efficacy and safety of various first-line initial treatment systemic regimens for patients with unresectable esophageal squamous carcinoma(ESCC), utilizing a network meta-analysis approach.MethodsA comprehensive search for randomized controlled trials focusing on the primary treatment of esophageal cancer ESCC was conducted across multiple databases including PubMed, Embase, Cochrane Library, and Web of Science, up until November 17, 2023. The quality of the included studies was rigorously assessed using Review Manager software. Subsequently, data analysis was meticulously carried out employing R software. The first-line treatment regimens examined were: CD (Cisplatin + Docetaxel), CET-CF (Cetuximab + Cisplatin + Fluorouracil), CF (Cisplatin + Fluorouracil), N-CF (Nivolumab + Cisplatin + Fluorouracil), NI (Nivolumab + Ipilimumab), Nim-CF (Nimotuzumab + Cisplatin + Fluorouracil), P-CF (Pembrolizumab + Cisplatin + Fluorouracil), and Ser-CF (Serplulimab + Cisplatin + Fluorouracil). The Primary endpoints included the overall survival(OS),progression-free survival (PFS),objective response rate (ORR) and disease control rate (DCR).The secondary endpoint was adverse effects(AEs).ResultsThe analysis encompassed eight studies, incorporating a total of 3,051 patients with untreated esophageal cancer. There are 45 people in the CD regimen,32 in the CET-CF regimen,1,212 in the CF regimen,447 in the N-CF regimen,456 in the NI regimen,53 in the Nim-CF regimen,447 in the P-CF regimen and 368 in the Ser-CF regimen. The network meta-analysis revealed that, in comparison to the CF regimen, the other regimens (CD, CET-CF, N-CF, NI, Nim-CF, P-CF, and Ser-CF) did not demonstrate a statistically significant impact on overall survival (OS) or progression-free survival (PFS). However, Ser-CF potentially offers superior outcomes in terms of OS and PFS when juxtaposed with other regimens. Notably, N-CF was associated with a substantial increase in the objective response rate (ORR), and CET-CF markedly improved the disease control rate (DCR). In terms of adverse effects, N-CF was more likely to cause anorexia, whereas CET-CF was significantly associated with nausea, vomiting, neutropenia, and skin disorders.ConclusionThe current evidence suggests that N-CF may provide the most favorable outcomes in terms of ORR, while CET-CF could be the optimal choice for enhancing DCR in patients with untreated esophageal cancer.